Features of acoustic resonance in iron borate - Skibinsky, K.M.; Strugatsky, M.B.; Yagupov, S.V.; Yevstafyev, A.I.; Preobrazensky, V.L.; Berzansky, V.N. (Functional Materials, 2014)
Acoustic resonance in a weak-ferromagnetic iron borate monocrystal was investigated. It was shown that observed field dependence of positions and magnitudes of the resonance peaks can be explained within framework of the developed theory of magnetic birefringence of sound in the inhomogeneous magnetized sample.